A Comparison of Parent and Child Narratives of Children's Recovery From Trauma. (March 2016) - Alisic, Eva; Krishna, Revathi N.; Robbins, Megan L.; Mehl, Matthias R.
Little is known about correspondence between parents' and children's narratives after a child's exposure to trauma. We examined 24 parent and child narratives of a child's recovery using Linguistic Inquiry and Word Count, a software program that yields the percentage of words that fall into linguistic categories (e.g., personal pronouns) and psychological categories (e.g., emotion words). Analyses revealed significant parent–child associations for number of words, rate of cognitive processing words, and rate of anxiety words. No associations were found for anger or sadness words. With both similarities and differences in parents' and children's narratives, the current findings encourage further research in the domain of posttrauma narratives.